Neutrophilic dermatosis of the dorsal hands related to cocaine abuse, - Marcial Álvarez-Salafranca; Mar García-García; Begoña de Escalante Yangüela (Sociedade Brasileira de Dermatologia, 2021)
Abstract Neutrophilic dermatoses encompass a wide spectrum of diseases characterized by a dense infiltration mainly composed of neutrophils. Neutrophilic dermatosis of the dorsal hands is currently considered a localized variant of Sweet syndrome. Cocaine abuse has been related to a wide range of mucocutaneous manifestations, including neutrophilic dermatoses such as pyoderma gangrenosum. The authors of this study present a patient with neutrophilic dermatosis of the dorsal hands, in which cocaine abuse was identified as a probable trigger.